2019
DOI: 10.1016/j.isci.2019.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Giant Electroresistance in Ferroionic Tunnel Junctions

Abstract: Summary Oxide-based resistive switching devices, including ferroelectric tunnel junctions and resistance random access memory, are promising candidates for the next-generation non-volatile memory technology. In this work, we propose a ferroionic tunnel junction to realize a giant electroresistance. It functions as a ferroelectric tunnel junction at low resistance state and as a Schottky junction at high resistance state, due to interface engineering through the field-induced migration of oxygen vaca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 49 publications
2
58
0
Order By: Relevance
“…We confirmed the dominant role of ferroelectric domain switching in the BTO‐based FTJs grown under high oxygen pressures, by comparing to nonferroelectric SrTiO 3 (STO)‐based devices . Figure a exhibits the evolution of conductance‐voltage ( G–V ) hysteresis loops as the pulse width varies while keeping the voltage range between ‐3.4 and +2.2 V. The conductance of LRS increases gradually as the pulse width increases, and eventually, a saturation value is reached when the pulse width is more than 10 ms.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…We confirmed the dominant role of ferroelectric domain switching in the BTO‐based FTJs grown under high oxygen pressures, by comparing to nonferroelectric SrTiO 3 (STO)‐based devices . Figure a exhibits the evolution of conductance‐voltage ( G–V ) hysteresis loops as the pulse width varies while keeping the voltage range between ‐3.4 and +2.2 V. The conductance of LRS increases gradually as the pulse width increases, and eventually, a saturation value is reached when the pulse width is more than 10 ms.…”
supporting
confidence: 57%
“…Local hysteretic behaviors of the PFM phase and amplitude signals were collected in DART (dual A.C. resonance tracking) mode and the signals were recorded while the voltage was off. High quality of BTO epitaxial films was confirmed by scanning transmission electron microscopy measurements …”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…Typically, this approach relies on the use of narrow (100 ns) pulse sequences to switch ferroelectric polarization and avoid the drift of oxygen vacancies. Other authors have shown large hysteretic resistance changes in ferroelectric tunnel junctions resulting from the drift of oxygen vacancies [19,20]. Furthermore, samples produced with high intentional concentration of oxygen vacancies display reversed polarity (resistive) switching to the ferroelectric switching found in similar samples with low vacancy concentration [21].…”
mentioning
confidence: 94%
“…Various efforts such as strain [24] , electrode/barrier interface engineering [18,20] and functional electrode [17] have been introduced to increase the TER OFF/ON ratio in these oxide FTJs [25] . The TER OFF/ON ratio can be as large as 10 7 at room temperature [26] . In addition, using ferromagnetic metals as electrodes, enable a nonvolatile control of electronic and spintronic responses in multifunctional devices [27][28][29][30][31] .…”
Section: Ferroelectric Synapses Based On Ftjs 21 History Of Ftjsmentioning
confidence: 99%